THE COGNITIVE PORTRAIT OF LITHUANIAN “GĖDA” IN PROVERBS - Bogdzevič , Monika (Proverbium - Yearbook, 2020)
The article provides a glimpse at wider research on the conceptualization of shame, fear and anger in Lithuanian. In the paper an attempt has been made to present the semantic and axiological substance of GĖDA1 (Eng. shame, embarrassment) encoded in the consciousness of the Lithuanian linguistic-cultural community. The cognitive portrait2 of Lithuanian GĖDA has been construed by applying SAT methodology, proposed by Jerzy Bartmiński. The data have been drawn from dictionaries and proverbs collected from the compendium of Lithuanian proverbs by searching for the conceptual and lexical keys3 of GĖDA. The conceptual key sketches the semantic core of GĖDA, and the lexical key reflects its textual potential, giving an insight into its ethno-conceptualization. Thus, the construal of the mental image of GĖDA illustrated in the Lithuanian proverbs under study draws on the dictionary definitions of the GĖDA lexemes, and on a semantic analysis of the proverbs containing those lexemes. The study focuses on the presentation of the cognitive portrait of Lithuanian GĖDA.